B2 bradykinin receptor antagonists: adsorption mechanism on electrochemically roughened Ag substrate. (22nd November 2012) - Proniewicz, Edyta; Skołuba, Dominika; Kudelski, Andrzej; Sobolewski, Dariusz; Prahl, Adam; Kim, Younkyoo; Proniewicz, Leonard M.
<x xml:space="preserve">Abstract</x> In this paper, the surface‐enhanced Raman scattering (SERS) spectra of the potent B2 bradykinin receptor antagonists, [D‐Arg0, Hyp3, Thi5, 8, L‐Pip7]BK, Aaa[D‐Arg0, Hyp3, Thi5, 8, L‐Pip7]BK, [D‐Arg0, Hyp3, Thi5, D‐Phe7, L‐Pip8]BK, and Aaa[D‐Arg0, Hyp3, Thi5, D‐Phe7, L‐Pip8]BK, were measured when immobilized onto a highly specific electrochemically roughened SERS‐active Ag substrate characterized by the formation of a 50 – 150 nm Ag islands on its surface. The observed SERS bands corresponding to different vibrational modes of the molecule, attached to or near Ag, and the variations in these bands resulting from competitive interactions of the functional groups of the peptides with the SERS‐active Ag surfaces and reorientation occurring over time of adsorption were analyzed in this study. Copyright © 2012 John Wiley & Sons, Ltd.